Refined Experts: Improving Classification in Large Taxonomies - Bennett, Paul; Nguyen, Nam (Proceedings of the 32nd Annual ACM SIGIR Conference, 2009)
While large-scale taxonomies – especially for web pages – have been in existence for some time, approaches to automatically classify documents into these taxonomies have met with limited success compared to the more general progress made in text classification. We argue that this stems from three causes: increasing sparsity of training data at deeper nodes in the taxonomy, error propagation where a mistake made high in the hierarchy cannot be recovered, and increasingly complex decision surfaces in higher nodes in the hierarchy. While prior research has focused on the first problem, we introduce methods that target the latter two problems – first by biasing the training distribution to reduce error propagation and second by propagating up “first-guess” expert information in a bottom-up manner before making a refined top down choice. Finally, we present an empirical study demonstrating that the suggested changes lead to 10-30% improvements in F1 scores versus an accepted competitive baseline, hierarchical SVMs.